Molecular pathology : the molecular basis of human disease - Coleman, William B.; Tsongalis, Gregory J. (Academic Press is an imprint of Elsevier, 2018)
As the molecular basis of human disease becomes better characterized, and the implications for understanding the molecular basis of disease becomes realized through improved diagnostics and treatment, Molecular Pathology, Second Edition stands out as the most comprehensive textbook where molecular mechanisms represent the focus. It is uniquely concerned with the molecular basis of major human diseases and disease processes, presented in the context of traditional pathology, with implications for translational molecular medicine. The Second Edition of Molecular Pathology has been thoroughly updated to reflect seven years of exponential changes in the fields of genetics, molecular, and cell biology which molecular pathology translates in the practice of molecular medicine. The textbook is intended to serve as a multi-use textbook that would be appropriate as a classroom teaching tool for biomedical graduate students, medical students, allied health students, and others (such as advanced undergraduates). Further, this textbook will be valuable for pathology residents and other postdoctoral fellows that desire to advance their understanding of molecular mechanisms of disease beyond what they learned in medical/graduate school. In addition, this textbook is useful as a reference book for practicing basic scientists and physician scientists that perform disease-related basic science and translational research, who require a ready information resource on the molecular basis of various human diseases and disease states. Explores the principles and practice of molecular pathology: molecular pathogenesis, molecular mechanisms of disease, and how the molecular pathogenesis of disease parallels the evolution of the disease. Explains the practice of "molecular medicine" and the translational aspects of molecular pathology Teaches from the perspective of "integrative systems biology."